Proyecto de renovación urbana para el sector dedicado a la venta reparación de motocicletas y autopartes en la ciudad de Neiva – Huila. (2022)
This research contains an urban analysis of the downtown area of the city of Neiva, highlighting the polygon between Seventh career , Fourth Street and Circunvalar which we find as predominant land use the trade dedicated to the sale and repa avenue . Within ir of motorcycles and light vehicles and due to this trade, it is evident that within the area there is a great deficit of residence, therefore, these activities generate various environmental problems, economic and social. For this reason, it is sought th at with this research a proposal is generated where said economic activity and the existing dynamics in the sector are maintained, for which the proposal seeks renewal by generating new road profiles with an exclusive axis for public transport with parking bays and parking areas. of whereabouts, creating effective public space of 29m2 per inhabitant, connected by an environmental axis, a cycle path circuit and a linear park on the Rio del Oro with which direct interaction with the Magdalena River boardwalk is sought. New land uses and a mixture are proposed in which 392 commercial premises will be developed and, in the blocks, dedicated to housing, 7story highrise housing with 2,536 apartments and commercial premises on the first level, an equidistance is sought within of the sector with the design of three parking spaces in height and on the first floor a commercial plinth and bicycle rental points.